Coordination and Critical Mass in a Network Market - An Experimental Evaluation - Amir Etziony; Avi Weiss (Bar-Ilan University, Department of Economics, 2002)
In this paper we present the results of an experiment aimed at testing the ability of consumers to coordinate actions in a market in which network externalities are present. Such markets are characterized by the necessity for consumers to believe that a certain minimum number of people will buy the good (the critical mass) in order to make purchase worthwhile. In our experiment, subjects were asked offered the option of buying a good at a certain price. Subjects were told the value of the product, but this value depended on how many other subjects bought. The experiment was run under two treatments – when subjects were homogeneous in their values and when they were heterogeneous. In each case, there were treatments with low prices and with high prices. Interestingly, subjects found it easier to purchase when they were heterogeneous than when they were homogeneous. In particular, the only treatment in which cooperation was not usually attained was in the homogeneous treatment when the price was high. We attribute this to critical mass. In the high priced homogeneous treatment the critical mass for all players was high, thus leading to great risk in purchase. In the heterogeneous game the critical mass for the marginal player was also high, but the subject knew that the critical mass for higher value subjects was much lower and that those subjects would therefore be likely to buy. This made purchase less risky, allowing equilibrium to be reached. One implication is that a firm facing a critical mass problem can efficiently help convince consumers that critical mass will be obtained by subsidizing high critical mass consumers (low value consumers), since potential consumers will be likely to already be convinced about the purchase of low critical mass consumers.
Keywords: C91; D43; D11; 330; Networks; Critical Mass; Experimental Economics; Coordination